Integrated evaluation of intelligence and creativity - Guise Milian, Queila (2018)
There is a current need for psychological tests that can assess cognitive functioning through an integrative perspective. The purpose of this study was to collect validity evidence of the adult version of the Battery of Intelligence and Creativity. The sample was composed of 99 students (51 female), with ages ranging between 15 and 17. The battery is composed of five cognitive tests and one creative test. The following tests were used as external criteria: The Reasoning Tests Battery 5; Divided and Alternating Attention Tests and Torrance Tests. The results indicated significant correlations (p?.05) between the battery subtests with the intelligence criteria tests (.28 to .52) as well as creativity tests (.26 to .54). This battery was found to be a valid measure to evaluate intelligence and creativity.